Electrophysiological Profile Remodeling via Selective Suppression of Voltage-Gated Currents by CLN1/PPT1 Overexpression in Human Neuronal-Like Cells - Demontis, Gian Carlo; Pezzini, Francesco; Margari, Elisa; Bianchi, Marzia; Longoni, Biancamaria; Doccini, Stefano; Lalowski, Maciej Maurycy; Santorelli, Filippo Maria; Simonati, Alessandro (Frontiers in Cellular Neuroscience, 2020)
CLN1 disease (OMIM #256730) is an inherited neurological disorder of early childhood with epileptic seizures and premature death. It is associated with mutations in CLN1 coding for Palmitoyl-Protein Thioesterase 1 (PPT1), a lysosomal enzyme which affects the recycling and degradation of lipid-modified (S-acylated) proteins by removing palmitate residues. Transcriptomic evidence from a neuronal-like cellular model derived from differentiated SH-SY5Y cells disclosed the potential negative roles of CLN1 overexpression, affecting the elongation of neuronal processes and the expression of selected proteins of the synaptic region. Bioinformatic inquiries of transcriptomic data pinpointed a dysregulated expression of several genes coding for proteins related to voltage-gated ion channels, including subunits of calcium and potassium channels (VGCC and VGKC). In SH-SY5Y cells overexpressing CLN1 (SH-CLN1 cells), the resting potential and the membrane conductance in the range of voltages close to the resting potential were not affected. However, patch-clamp recordings indicated a reduction of Ba2+ currents through VGCC of SH-CLN1 cells; Ca2+ imaging revealed reduced Ca2+ influx in the same cellular setting. The results of the biochemical and morphological investigations of CACNA2D2/α2δ-2, an accessory subunit of VGCC, were in accordance with the downregulation of the corresponding gene and consistent with the hypothesis that a lower number of functional channels may reach the plasma membrane. The combined use of 4-AP and NS-1643, two drugs with opposing effects on Kv11 and Kv12 subfamilies of VGKC coded by the KCNH gene family, provides evidence for reduced functional Kv12 channels in SH-CLN1 cells, consistent with transcriptomic data indicating the downregulation of KCNH4. The lack of compelling evidence supporting the palmitoylation of many ion channels subunits investigated in this study stimulates inquiries about the role of PPT1 in the trafficking of channels to the plasma membrane. Altogether, these results indicate a reduction of functional voltage-gated ion channels in response to CLN1/PPT1 overexpression in differentiated SH-SY5Y cells and provide new insights into the altered neuronal excitability which may underlie the severe epileptic phenotype of CLN1 disease. It remains to be shown if remodeling of such functional channels on plasma membrane can occur as a downstream effect of CLN1 disease.